Determining the Association of Mean Platelet Volume in the Late First Trimester of Pregnancy and Development of Preeclampsia - Shailja S. Bhamri; Urmila Singh; Seema Mehrotra; Vandana Solanki (Current Innovations in Medicine and Medical Science Vol. 10, 2022)
The present study aimed to find out the correlation between the mean platelet volume in the late 1st trimester of pregnancy and development of a Preeclampsia later on. Preeclampsia (PE) is a pregnancy-specific medical disorder that is characterized by activation of the coagulation system, and endothelial cell dysfunction. This disorder is a major cause of maternal and fetal morbidity and mortality. It was a prospective cohort study in which 500 pregnant women (11–14 weeks of gestation) were enrolled and their mean platelet volume (MPV) was measured. They were followed till delivery. MPV of pre-eclamptic and normotensive women was compared. MPV of pre-eclamptic women was significantly higher than that of the normotensive women (p = 0.001). MPV > 10.55 fL was found to be 68.7% sensitive and 55.9% specific for the prediction of Preeclampsia with a negative predictive value of 87.6%. Thestudy suggest conducting future research with a large sample size to investigate the combination of mean platelet volume with other cost-effective markers in order to increase the sensitivity and specificity of preeclampsia prediction without adding additional financial burden to expectant mothers, particularly in low-resource settings.